Pengembangan Keterampilan 21st Century dalam Pendidikan Islam - M. Yusuf; Mohamad Sodik (Universitas Islam Balitar, 2025)
This article explores the development of 21st-century skills in the context of Islamic education, addressing common challenges faced by educational institutions. Aligned with the dynamics of globalization and technological advancement, the significance of critical, creative, and collaborative thinking skills in education is becoming increasingly urgent. The research method applied is library research, involving a review of literature, articles, and related studies to elaborate on the concepts and practices of developing 21st-century skills in the context of Islamic education. The primary objective of this research is to identify effective strategies and pedagogical principles that can be adopted to enhance the quality of Islamic education in the contemporary era. The research findings highlight the need for the integration of Islamic values in the development of 21st-century skills, with a focus on critical thinking, creativity, collaboration, and digital literacy. This article makes a significant contribution to understanding how Islamic education can adapt to the dynamics of the times while preserving the values of Islamic identity. Artikel ini mengeksplorasi pengembangan keterampilan abad ke-21 dalam konteks pendidikan Islam, mengarahkan perhatian pada tantangan umum yang dihadapi oleh lembaga pendidikan. Sejalan dengan dinamika globalisasi dan kemajuan teknologi, pentingnya keterampilan berpikir kritis, kreatif, dan kolaboratif dalam pendidikan semakin mendesak. Metode penelitian yang diterapkan adalah library research, dengan melakukan tinjauan literatur, artikel, dan penelitian terkait untuk merinci konsep serta praktik pengembangan keterampilan 21st Century dalam konteks pendidikan Islam. Tujuan utama penelitian ini adalah mengidentifikasi strategi efektif dan prinsip pedagogis yang dapat diadopsi untuk meningkatkan kualitas pendidikan Islam di era kontemporer. Hasil penelitian menyoroti kebutuhan integrasi nilai-nilai Islam dalam pengembangan keterampilan 21st Century, sambil menitikberatkan pada kemampuan berpikir kritis, kreativitas, kolaborasi, dan literasi digital. Artikel ini memberikan kontribusi penting untuk memahami bagaimana pendidikan Islam dapat menyesuaikan diri dengan dinamika zaman, sekaligus mempertahankan nilai-nilai identitas Islam.